2002
DOI: 10.1007/s10038-002-8648-3
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic sequences of the tyrosinase gene: allele analysis on 16 OCA1 patients in Japan indicate that three polymorphic sequences in the tyrosinase gene promoter could be powerful markers for indirect gene diagnosis

Abstract: Since 1989, a large number of mutations of the tyrosinase gene, which result in oculocutaneous albinism (OCA), have been reported. However, approximately 15% of patients with tyrosinase-related OCA (OCA1) heterozygously carried an uncharacterized mutation, which presumably existed outside of the ordinarily examined area of the tyrosinase gene. In such cases, polymorphic sequence(s) of the tyrosinase gene might be useful to identify the OCA1 allele. In this study, we examined four polymorphic sequences of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…During this study, the missense substitution c.230G>A (p.Arg77Gln) was identified in exon 1 of TYR in five different families (1–3, 5 and 13). This mutation has also been been reported in Japanese, Korean, Chinese and German populations . The affected individuals of the five families have white hair, light‐coloured eyes and very pale skin, and at the time of the study were aged between 3 and 42 years.…”
Section: Discussionsupporting
confidence: 52%
“…During this study, the missense substitution c.230G>A (p.Arg77Gln) was identified in exon 1 of TYR in five different families (1–3, 5 and 13). This mutation has also been been reported in Japanese, Korean, Chinese and German populations . The affected individuals of the five families have white hair, light‐coloured eyes and very pale skin, and at the time of the study were aged between 3 and 42 years.…”
Section: Discussionsupporting
confidence: 52%
“…R278X is an exceptional and frequent mutation in several races and in the different places [12][13][14][15]. According to haplotype analysis, R278X had at least two different origins, which was thought to have occurred a long time in the past [16]. Our study is unique because we have found the R278X mutation in our patients from Hokkaido, whose inhabitants had moved from various districts of Japan in the 19th century.…”
Section: Resultsmentioning
confidence: 81%
“…This cross-sectional study was conducted in June 2014 by multistage and stratified cluster random sampling. Nineteen districts of Shanghai were stratified into central urban area, suburb and outer suburb according to the 2005 Shanghai census report 12 and seven districts were randomly chosen, including Jing’an, Changning, Zhabei, Jiading, Jinshan, Pudong and Chongming. From these, 26 general primary schools were randomly sampled from school lists and students in grades 1–5 were recruited ( figure 1 ).…”
Section: Methodsmentioning
confidence: 99%